The Influence of Leadership, Motivation and Job Satisfaction on Organizational Commitment - Rahma Muti'ah; Mulkan Ritonga (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to investigate the influence of leadership, motivation, and job satisfaction on organizational commitment. Effective leadership, high motivation, and good job satisfaction are considered key factors in shaping employee commitment to the organization. This study used a quantitative approach with a survey of office employees and PKS PT. Serba Huta Jaya as many as 63 people as a population as well as a research sample. Data was collected using questionnaires that measured leadership levels, motivation, job satisfaction, and organizational commitment. Data analysis was performed using descriptive statistical methods and multiple regression analysis to determine the relationship between these variables. The results showed a positive and significant relationship between leadership, motivation, and job satisfaction with organizational commitment both partially and simultaneously. This suggests that effective leaders, a motivating work environment, and high levels of job satisfaction can increase employee commitment to the organization. These findings have practical implications for human resource management in the development of strategies to increase organizational commitment. Managers and leaders need to pay attention to the importance of building effective leadership, creating a motivating work environment, and paying attention to employee job satisfaction as an effort to increase organizational commitment. Thus, the study contributes to the understanding of the factors influencing organizational commitment and provides a basis for the development of relevant management interventions in the workplace.